Analysis of Surface Defects on RAM BOP with Non-Destructive Testing and Crack Propagation Simulation to Detect Potential Crack Development - Fadhil Wibowo; Andoko Andoko; Yahya Zakaria (Institut Teknologi Adhi Tama Surabaya, Indonesia, 2026)
Blowout Preventers (BOPs) are critical safety devices in drilling operations and operate in abrasive, high‑pressure environments that accelerate wear and failure. This study applies two Non‑Destructive Testing (NDT) methods, Liquid Penetrant Testing (LPT) and Magnetic Particle Testing (MPT), to identify surface defects on RAM BOP components, and integrates finite‑element‑based crack propagation simulation to assess the risk of further damage. LPT was applied to coated/non‑ferromagnetic parts, while MPT was used for ferromagnetic components, referencing ASME Section V acceptance criteria. Inspections revealed defects including a 4.9 mm crack on the piston shaft and pitting corrosion (≈0.8-5.3 mm) on several parts (e.g., cavity upper, housing). The simulation, with 3000 psi operating pressure and an initial flaw (l = 3 mm; h = 1 mm; r = 0.6 mm), predicted stress concentration at the crack tip (up to 141 MPa) and potential growth toward 7.9-11.7 mm if unrepaired. Recommended actions include re‑welding cracked regions and polishing minor scratches/pitting, combined with periodic NDT for early detection. The integrated NDT-simulation workflow supports proactive maintenance, enhances operational safety, and mitigates failure risk.